2012
DOI: 10.1097/meg.0b013e3283513e69
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial

Abstract: A 48-week escalating dose of PEG-IFN2a is associated with a significant reduction in all-cause mortality and nononcological liver-related morbidity in this trial. Further investigation of PEG-IFN2a is warranted for patients with advanced HCV-related cirrhosis for whom there is no other treatment and where transplantation is associated with rapid progression to cirrhosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…In addition, DAA drugs have few adverse effects and improved tolerability, which are factors in patients completing the therapy . Literature on interferon-based therapy found that curing HCV infection was associated with improved clinical outcomes, such as a decrease in the incidence of hepatocellular cancer and a decrease in mortality rate . More individuals with HCV infection are expected to have these outcomes if treated with DAA drugs, given the higher cure and completion rates associated with DAA therapy.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, DAA drugs have few adverse effects and improved tolerability, which are factors in patients completing the therapy . Literature on interferon-based therapy found that curing HCV infection was associated with improved clinical outcomes, such as a decrease in the incidence of hepatocellular cancer and a decrease in mortality rate . More individuals with HCV infection are expected to have these outcomes if treated with DAA drugs, given the higher cure and completion rates associated with DAA therapy.…”
Section: Introductionmentioning
confidence: 99%